Transient gene expression in transformed banana (Musa cv. Bluggoe) protoplasts and embryogenic cell suspensions - Sagi, L.; Remy, S.; Verelst, B.; Panis, Bartholomeus; Cammue, B.P.A.; Volckaert, G.; Swennen, Rony L. (1995)
In order to introduce currently-available genes with agronomical value into banana, two genetic transformation protocols have been optimized. Firstly, regenerable protoplasts isolated from embryogenic cell suspensions of the cultivar Bluggoe have been used for the introduction of several chimaeric uidA gene constructs by electroporation. With the inclusion of polyethylene glycol and heat shock, the frequency of transiently expressing protoplasts reached 1.8% as shown by an in situ β-glucuronidase assay. A duplicated 35S promoter with an alfalfa mosaic virus leader sequence (pBI-426) induced the highest expression rate among the constructs tested. Embryogenic cell suspensions of cv. Bluggoe have also been bombarded with accelerated particles coated with a high expression uidA gene construct (pEmuGN) using a biolistic gun. After a partial optimization of the procedure, transient GUS assays reproducibly demonstrated the presence of 400 blue foci in 30 μl of settled cell volume (approximately 25 mg cells). Selection and characterization of antibiotic-resistant transformed cultures is in progress.